A Neuro-Sliding Mode Controller for STATCOM - Morris, Stella (2004)
The paper presents a new controller design for STATCOM for damping electromechanical oscillations in a power system. The STATCOM is modeled as a reactive current source and the magnitude of this current is obtained by using a sliding mode control strategy. The parameters of the sliding mode controller (SMC) are obtained using linearised model of single-machine infinite-bus power system and a pole placement technique. In order to. avoid repeated computation of the sliding mode control gains at different operating conditions, a single neuron controller is used to adapt the parameters of the SMC. Several simulation results are presented to show the marked improvement in transient stability enhancement of the single-machine infinite-bus and multimachine power systems over a wide range of operating conditions.